2009
DOI: 10.1103/physrevstab.12.100701
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid planar free-electron maser in the magnetoresonance regime

Abstract: We study the operation regime of a hybrid planar free-electron maser (FEM) amplifier near the magnetoresonant value of the uniform longitudinal (guide) magnetic field. Using analytical expressions for individual test electron trajectories and normal frequencies of their three-dimensional oscillations in the magnetostatic field of the hybrid planar FEM, an analytical condition of chaotization of motion is established and shown to be given by the Chirikov resonance-overlap criterion applied to the normal undulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…2 and 3 gives a clear indication that the adiabatic undulator entrance "improve integrability" of the nonlinear dynamical system (15) and reduce the width of chaotic regions. In [17] it was found that the initial positive value for the x-component of the velocity leads to the suppression of the chaotic region. A test electron acquires such a positive average correction to v x passing through the region of the adiabatic entrance.…”
Section: B Superconvergent Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…2 and 3 gives a clear indication that the adiabatic undulator entrance "improve integrability" of the nonlinear dynamical system (15) and reduce the width of chaotic regions. In [17] it was found that the initial positive value for the x-component of the velocity leads to the suppression of the chaotic region. A test electron acquires such a positive average correction to v x passing through the region of the adiabatic entrance.…”
Section: B Superconvergent Methodsmentioning
confidence: 99%
“…Since the relativistic electron-wave interaction is being studied, the nonradiated fields (space-charge fields) are supposed to be negligible. The relativistic effects result in that the force f m caused by the nonradiated magnetic field partially suppresses the defocusing action of the transversal part of the force f caused by the rotational part of the nonradiated electric field (see [17] for details).…”
Section: The Theoretical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Hitherto, enthusiasm for the FEL configuration with a positive or a reversed guide magnetic field is in continuance. [10][11][12][13] Since the amplified wave energy in a FEL comes from the kinetic energy of the electron beam, motion of the equilibrium electrons substantially affects both the transportation quality of the electron beam and consequently the gain and output power of the wave. Although a great deal of literature has been devoted to this subject and achievements have been made, to the present day there still exist some fundamental questions suspending.…”
Section: Introductionmentioning
confidence: 99%